2015
DOI: 10.1007/s11916-015-0483-2
|View full text |Cite
|
Sign up to set email alerts
|

High-Altitude Headache

Abstract: High-altitude headache is one of many neurological symptoms associated with the ascent to high altitudes. Cellular hypoxia due to decreased barometric pressure seems to be the common final pathway for headache as altitude increases. Susceptibility to high-altitude headache depends on genetic factors, history of migraine, and acclimatization, but symptoms of acute mountain sickness are universal at very high altitudes. This review summarizes the pathophysiology of acute mountain sickness and high-altitude heada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 71 publications
0
17
2
Order By: Relevance
“…We detected a HAH incidence of 72.6% after high-altitude exposure in the current study, slightly lower than the incidence in previous studies [3,4]. One possible reason is that subjects are general young soldiers, and they take exercise and military training regularly, resulting in better physical fitness and hypoxia tolerance.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…We detected a HAH incidence of 72.6% after high-altitude exposure in the current study, slightly lower than the incidence in previous studies [3,4]. One possible reason is that subjects are general young soldiers, and they take exercise and military training regularly, resulting in better physical fitness and hypoxia tolerance.…”
Section: Discussioncontrasting
confidence: 75%
“…High-altitude headache (HAH) is the most frequent complaint in lowlanders who ascend from plain area to high altitude and occurs either as an isolated symptom or as a part of acute mountain sickness (AMS) [1][2][3][4]. According to Lake Louise AMS scoring system revised in 2018, headache is an indispensable symptom [5].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have considered the relationship between migraine or headache and environmental factors such as weather. High altitude is a proven trigger of headache especially during rapid ascents (67). Living at high altitudes may cause chronic headache, especially in those lacking genetic adaptations to adapt to hypoxia (68).…”
Section: Weather Triggers In Migrainementioning
confidence: 99%
“…Gamboa et al [12] also reported that there was an association between depression and migraine in HA population. Migraine as altitude increases may be result from cellular hypoxia due to decreased barometric pressure [43]. The relationship between migraine and depression may be bidirectional, and genes from serotonergic and dopaminergic may be associated with the aetiology of both migraine and depression [42].…”
Section: Discussionmentioning
confidence: 99%